Does Calretinin Immunohistochemistry Reduce Inconclusive Diagnosis in Rectal Biopsies for Hirschsprung Disease? - Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Takegawa, Bonifácio Katsunori [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Terra, Simone A. [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Lippincott Williams & Wilkins, 2014)
Many difficulties occur during the evaluation of rectal biopsies for the diagnosis of Hirschsprung disease. We investigated whether the introduction of calretinin (CR) immunohistochemistry in a diagnostic panel could decrease the rate of inconclusive results. Data from 82 patients undergoing rectal biopsies before and after CR introduction were analyzed. Inconclusive results were obtained in 17 of 45 rectal biopsies (37.8%) in the series of cases before CR introduction and in 5 of 42 rectal biopsies (11.9%) in the series of cases after CR (P < 0.006). The inclusion of CR in the histopathologic panel may improve the diagnostic accuracy of Hirschsprung disease.
Keywords: Hirschsprung disease; rectal suction biopsies; calretinin immunohistochemistry